Noah Barleywater runs away : a fairytale - Boyne, John, 1971- (Yearling, 2012)
When life at home becomes too difficult, eight-year-old Noah sets out to see the world and have an adventure, and in the forest he meets a toymaker who has a story and some advice to share.